The role of retinoic acid receptor-related orphan receptors in skeletal diseases - Zhang, Yifan; Ma, Jun; Bao, Xingfu; Hu, Min; Wei, Xiaoxi (Frontiers in Endocrinology, 2023)
Bone homeostasis, depending on the balance between bone formation and bone resorption, is responsible for maintaining the proper structure and function of the skeletal system. As an important group of transcription factors, retinoic acid receptor-related orphan receptors (RORs) have been reported to play important roles in bone homeostasis by regulating the transcription of target genes in skeletal cells. On the other hand, the dysregulation of RORs often leads to various skeletal diseases such as osteoporosis, rheumatoid arthritis (RA), and osteoarthritis (OA). Herein, we summarized the roles and mechanisms of RORs in skeletal diseases, aiming to provide evidence for potential therapeutic strategies.